Designing substitution boxes for secure ciphers. (26th April 2007) - Nedjah, Nadia; Mourelle, Luiza de Macedo
In cryptography, a Substitution box (S-box) constitutes a cornerstone component of symmetric key algorithms. In block ciphers, they are typically used to obscure the relationship between the plaintext and the ciphertext. It is well-known that the more linear and the less auto-correlated the S-box is, the more resilient the cryptosystem that uses them. However, engineering a regular S-box that has the highest non-linearity and lowest auto-correlation properties is an NP-complete problem. In this paper, we exploit evolutionary computation to engineer regular S-boxes that present high non-linearity and low auto-correlation properties.